Legalidade ou discricionariedade na governança de bancos públicos: uma análise aplicada ao caso do BNDES - Schapiro, Mario Gomes (2017)
This article aims at evaluating the institutional design of the political delegation that shapes The Brazilian Development Bank's (BNDES) financial activities. It employs a normative framework of administrative law, concerning the types of political delegation, and studies two of them: legality and discretion. Legal governance is a type of arrangement in which policy objectives are delegated by the Congress, while discretionary public governance policy objectives are defined in the Executive branch of government. Both types have different comparative advantages in governing policies. Whereas legality favors predictability and publicity, discretion enables flexibility and less political involvement. The main claim is that, due to Brazil's institutional environment, discretionary governance has proven advantageous. BNDES has been kept from the games of political and parliamentary clientele and it has suitable operational flexibility to act in times of economic crisis. However, this configuration also has costs, including financial agenda opacity and social accountability deficits.